Corporate Social and Environmental Strategy and Reporting in Indonesian Plantation Industry - Intan Belinda Lestari; Noradiva Hamzah; Ruhanita Maelah (Universitas Pasundan, 2019)
This study aims to investigate how corporate social and environmental strategy can contribute to corporate social and environmental reporting (CSER) in the plantation industry in Indonesia. This study employed a case study approach by using semi–structured interviews to collect data from Indonesian plantation companies listed in the Indonesia Stock Exchange (IDX) and state–owned plantation companies that included CSER in their annual report. The motivation of CSER implementation in Indonesian plantation companies was influenced by proactive and reactive strategies. The corporate social and environmental strategy of proactive principles would publish CSER due to the social discretion beyond the regulatory requirements or pressure of certain stakeholders, and prior to any negative information being received by the public. Moreover, the corporate social and environmental strategy of reactive principles would also publish CSER to meet stakeholders’ needs and demands, obtain good corporate image and reputation, and avoid negative impacts (e.g., harm, hazards, mishap, complaints, etc.). Therefore, corporate social and environmental strategy can contribute to CSER depending on whether the company has proactive or reactive principles. This research contributes to the knowledge of social accounting literature in which CSER practices can be influenced by corporate social and environmental strategy.